2023
DOI: 10.3390/ijerph20166558
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life, Stress, Caregiving Burden and Special Needs of Parents Caring for a Short-Statured Child—Review and Recommendations for Future Research

Abstract: Children with short stature can experience a range of burdens due to their chronic condition. However, little is known about parents’ experiences dealing with their child’s short stature and the potential caregiving burdens and concerns they may face. We aim to review the literature on health-related quality of life (HRQOL), caregiving burden, and special needs among parents caring for a child with isolated growth hormone deficiency (IGHD) or idiopathic short stature (ISS). Using pre-defined inclusion and excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
0
0
0
Order By: Relevance
“…In this aspect, smokers with elevated stress levels frequently consider themselves as less healthy, have a poor sense of self-worth, and are more likely to engage in harmful lifestyle choices such as increased alcohol consumption/binge drinking, unsafe sex, usage of drugs, and heavy cigarette use [19]. Furthermore, smoking and stress levels have been linked to a variety of adverse consequences, including depression and anxiety [10,19]. Consequently, sadness, emptiness, anhedonia, poor self-care, poor focus, loss of capacity to function, sleep difficulties, feelings of worthlessness, and recurrent suicidal ideation are common in smokers with depression [13].…”
Section: Smoking Effects Onmentioning
confidence: 99%
See 2 more Smart Citations
“…In this aspect, smokers with elevated stress levels frequently consider themselves as less healthy, have a poor sense of self-worth, and are more likely to engage in harmful lifestyle choices such as increased alcohol consumption/binge drinking, unsafe sex, usage of drugs, and heavy cigarette use [19]. Furthermore, smoking and stress levels have been linked to a variety of adverse consequences, including depression and anxiety [10,19]. Consequently, sadness, emptiness, anhedonia, poor self-care, poor focus, loss of capacity to function, sleep difficulties, feelings of worthlessness, and recurrent suicidal ideation are common in smokers with depression [13].…”
Section: Smoking Effects Onmentioning
confidence: 99%
“…Various studies have reported that smokers are underweight {lower body mass index (BMI)} when compared to non-smokers [10,19,30]. However, evidence suggests that smokers suffer from developing central fat accumulation, mostly seen among female smokers [30].…”
Section: Smoking and Body Compositionmentioning
confidence: 99%
See 1 more Smart Citation